2016
DOI: 10.1016/s1002-0160(15)60074-1
|View full text |Cite
|
Sign up to set email alerts
|

Redistribution of Soil Organic Carbon Triggered by Erosion at Field Scale Under Subhumid Climate, Hungary

Abstract: Soil organic carbon (SOC) has primary importance in terms of soil physics, fertility and even of climate change control. An intensively cultivated Cambisol was studied in order to quantify SOC redistribution under subhumid climate. One hundred soil samples were taken from the representative points of the solum along the slopes from the depth of 20-300 cm with a mean 1.2 % SOC content. They were measured by the simultaneous application of diffuse reflectance (240-1900 nm) and traditional physico-chemical method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 51 publications
1
21
0
4
Order By: Relevance
“…Many studies report data on SOC enrichment down-slope (Wang et al 2010;Farsang et al 2012). Szalai et al (2016) found SOC deposition spots on the toe-slope of the same research site. This suggests that beyond mass movement spatial heterogeneity of selective SOM deposition or mineralization may hardly affect local SOC contents.…”
Section: Resultsmentioning
confidence: 77%
See 3 more Smart Citations
“…Many studies report data on SOC enrichment down-slope (Wang et al 2010;Farsang et al 2012). Szalai et al (2016) found SOC deposition spots on the toe-slope of the same research site. This suggests that beyond mass movement spatial heterogeneity of selective SOM deposition or mineralization may hardly affect local SOC contents.…”
Section: Resultsmentioning
confidence: 77%
“…1). Previous investigations demonstrated that this field site was representative of local cropland and suitable for historical soil erosion studies Szalai et al 2016). Moreover, landscapes with very similar properties and processes are widespread in Western and Central Europe, where soil erosion became serious due to forest clearance in historical times (Cerdan et al 2010).…”
Section: Study Sitementioning
confidence: 94%
See 2 more Smart Citations
“…Previously, field scale erosional studies were done by Szalai et al (2016) and detailed aggregate related laboratory scale soil loss was also studied by Szabó et al (2015). The current study concentrates on erosional response of the soil in case of the slopes (2; 5; 12% steepness) and surface status (Table 1.)…”
Section: Methodsmentioning
confidence: 99%